COMPOSITION. COMPOSITION IN SPEECH TYPES - A. Dadajonov,E. O‘rinboyeva (International Journal of Literature and Language Studies, 2026)
This article examines the theoretical foundations of speech composition and analyzes its specific compositional structures in different speech types, namely narration, description, and reasoning. The study substantiates the relationship between speech composition and the speaker’s communicative purpose, content, and genre characteristics. Particular attention is paid to the compositional model proposed by M. F. Quintilian and its interpretation in modern linguistic studies. Furthermore, the logical and structural characteristics of reasoning discourse are explored, with special emphasis on the role of argumentation and conclusion in text organization.